Feasibility and safety of endoscopic submucosal dissection for lesions involving the ileocecal valve - Yoshizaki, Tetsuya; Toyonaga, Takashi; Tanaka, Shinwa; Ohara, Yoshiko; Kawara, Fumiaki; Baba, Shinichi; Tsubouchi, Eiji; Takihara, Hiroshi; Watanabe, Daisuke; Ishida, Tsukasa; Hoshi, Namiko; Morita, Yoshinori; Umegaki, Eiji; Azuma, Takeshi (Endoscopy, 2016)
Background and study aim: Endoscopic submucosal dissection (ESD) has been applied to treat early colorectal cancers. The aim of this study was to clarify the clinical course of ESD for lesions involving the ileocecal valve (ICV) by evaluating the successful resection rates, and the risk and frequency of adverse events.Patients and methods: The outcome of ESD on 38 ICV lesions was compared with the outcome of 132 cecal lesions that did not involve the ICV or appendiceal orifice during the same study period. The factors related to longer procedure time, postoperative stricture development, and tumor recurrence were investigated for ESD of ICV lesions.Results: There was no significant difference between the ICV and non-ICV groups in the en block resection rates. The median procedure time was significantly longer in the ICV group than in the non-ICV group, with a point estimate of the difference of 37 minutes (95 % confidence interval [CI] 20.00 to 56.00; P  < 0.01). None of the patients developed symptomatic post-ESD stricture or tumor recurrence. ESD procedure duration was ≥ 120 minutes in 16 lesions and < 120 minutes in 22 lesions of the ICV group. A specimen diameter of ≥ 40 mm and tumor extension into terminal ileum were factors related to a longer procedure time (odds ratio [OR] 8.40, 95 %CI 1.53 to 46.10, P = 0.01; OR 10.60, 95 %CI 2.17 to 51.40, P  < 0.01, respectively).Conclusions: ICV lesions can be resected by ESD without major adverse events or causing symptomatic stricture development. However, ESD for ICV lesions should be performed only by expert endoscopists, as the procedure requires accomplished endoscopic skill and experience.